2014
DOI: 10.1128/jvi.02591-13
|View full text |Cite|
|
Sign up to set email alerts
|

PLC-γ1 Signaling Plays a Subtype-Specific Role in Postbinding Cell Entry of Influenza A Virus

Abstract: Host signaling pathways and cellular proteins play important roles in the influenza viral life cycle and can serve as antiviral targets. In this study, we report the engagement of host phosphoinositide-specific phospholipase ␥1 (PLC-␥1) in mediating cell entry of influenza virus H1N1 but not H3N2 subtype. Both PLC-␥1-specific inhibitor and short hairpin RNA (shRNA) strongly suppress the replication of H1N1 but not H3N2 viruses in cell culture, suggesting that PLC-␥1 plays an important subtype-specific role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
0
32
1
1
Order By: Relevance
“…3A , the Cryptoporus volvatus extract did not affect the quantity of infectious virus particles that can attach to host membranes. To test whether the Cryptoporus volvatus extract acts at the internalization stage of infection, we used an assay described before [32] . Influenza viruses were allowed to bind MDCK cells at 4°C for 1 h. Then the inoculum was replaced with fresh DMEM medium containing the Cryptoporus volvatus extract, and the cells were transferred to 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…3A , the Cryptoporus volvatus extract did not affect the quantity of infectious virus particles that can attach to host membranes. To test whether the Cryptoporus volvatus extract acts at the internalization stage of infection, we used an assay described before [32] . Influenza viruses were allowed to bind MDCK cells at 4°C for 1 h. Then the inoculum was replaced with fresh DMEM medium containing the Cryptoporus volvatus extract, and the cells were transferred to 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of these factors was mostly demonstrated in a limited number of IAV subtypes, such as H1N1 or H3N2. Moreover, it has been reported that distinct signaling pathways are specifically activated by different IAV subtypes to facilitate virus internalization (15,51). These facts prompted us to investigate potential cofactors involved in the entry of H5N1 virus into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of terminal N-linked glycosylation due to a mutation in the GNT1 gene arrests IAV internalization at the plasma membrane before the virus is endocytosed (12). Plasma membrane lipid raft clustering, caused by IAV attachment, activates epidermal growth factor receptor (EGFR) (13), leading to the activation of downstream signaling molecules, such as phosphatidylinositol 3-kinase (PI3K) and phospholipase C ␥1 (PLC-␥1) (14,15), which enhances IAV uptake. CD81 promotes the trafficking of IAV to fusion-competent endosomes and further organizes the endosomal membrane to assist viral fusion (16).…”
Section: Importancementioning
confidence: 99%
“…Interestingly, EGFR-dependent phosphorylation of PLC-␥1 occurs only in response to infection with IAV of the H1N1 subtype but not with H3N2 viruses (57). Indeed, activation of PLC-␥1 positively influenced virus internalization (48,57). These data allow for speculation that the precise internalization routes might differ between IAV subtypes.…”
Section: Sialoglycan-dependent Coreceptorsmentioning
confidence: 94%
“…Another enzyme downstream of EGFR involved in IAV entry is phospholipase C-␥1 (PLC-␥1). Interestingly, EGFR-dependent phosphorylation of PLC-␥1 occurs only in response to infection with IAV of the H1N1 subtype but not with H3N2 viruses (57). Indeed, activation of PLC-␥1 positively influenced virus internalization (48,57).…”
Section: Sialoglycan-dependent Coreceptorsmentioning
confidence: 99%